The impact of heat treatment on the magnetic sensitivity of irradiated by electrons single crystals n-Ge - Luniov, S.V.; Zimych, A.I.; Khvyshchun, M.V.; Maslyuk, V.T.; Megela, I.G. (Functional Materials, 2019)
Isothermal annealing of n-Ge single crystals irradiated by the electron flux Ω = 5·10¹⁵ el./cm², energy of 10 MeV, has been investigated. Dependences of Hall voltage on the magnitude of the external magnetic field in the range from 0 to 0.5 T are obtained by Hall effect measurements. Coefficients of the magnetic sensitivity for irradiated single crystals n-Ge before and after annealing at different temperatures were also determined. The abnormal annealing at the temperature of 403 K has been revealed. Hall constant was being increased during this process, and the maximal magnetic sensitivity was being achieved correspondingly. The given effect is explained by the increasing concentration of radiation defects with deep energy levels (A-centers) owing to the generation of vacancies which are formed in annealing of kernels of regions disordering. Such abnormal annealing can be used as a tool to create highly sensitive Hall sensors by the irradiated n-Ge.